2010
DOI: 10.1007/s00535-010-0336-z
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol drinking patterns and the risk of fatty liver in Japanese men

Abstract: Our observations suggest that alcohol consumption plays a protective role against FL in men, and consistent alcohol consumption may contribute to this favorable effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 36 publications
(46 reference statements)
1
48
2
Order By: Relevance
“…In a cross-sectional study in Japanese men, low alcohol consumption (40-140 g/week) significantly reduced the incidence of fatty liver (AOR = 0.824 [95% CI 0.683-0.994]) [20]. We have also found that alcohol intake may inhibit the development of fatty liver through an association of alcohol drinking pattern with obesity [48]. In the current study, intake of a small amount of alcohol had an inhibitory effect on NAFLD development in multivariate analysis that included the number of metabolic syndrome risk factors as a variable (Table 5).…”
Section: Discussionmentioning
confidence: 77%
“…In a cross-sectional study in Japanese men, low alcohol consumption (40-140 g/week) significantly reduced the incidence of fatty liver (AOR = 0.824 [95% CI 0.683-0.994]) [20]. We have also found that alcohol intake may inhibit the development of fatty liver through an association of alcohol drinking pattern with obesity [48]. In the current study, intake of a small amount of alcohol had an inhibitory effect on NAFLD development in multivariate analysis that included the number of metabolic syndrome risk factors as a variable (Table 5).…”
Section: Discussionmentioning
confidence: 77%
“…[2][3][4][5][6][7][8][9] In conclusion, quantitative evidence showed that MAC is associated with a significant protective effect of about 31% on the risk of having NAFLD. Even more remarkable, MAC was associated with an average protective effect of about 50% on the risk of developing an advanced disease stage.…”
Section: Is Mac Associated With Lower Prevalence Of Nash Among Those mentioning
confidence: 79%
“…Then, 19 English and four Chinese studies remained for complete evaluation, four Chinese studies were excluded due to design weakness or low quality data, two English studies were excluded due to a lack of data for calculation, and one English study was discarded due to duplication. In the end, 16 observational articles with a total of 76,608 participants including 39,198 nondrinkers, 31,942 light to moderate drinkers (LM drinkers), and 5,468 heavy drinkers met our inclusion criteria (Dunn, Xu & Schwimmer, 2008; Cotrim et al, 2009; Gunji et al, 2009; Yamada et al, 2010; Hiramine et al, 2011; Dunn et al, 2012; Hamaguchi et al, 2012; Wong et al, 2012; Moriya et al, 2013; Sookoian, Castaño & Pirola, 2014; Hashimoto et al, 2015; Kächele et al, 2015; Lau et al, 2015; Moriya et al, 2015; Nishioji et al, 2015; Sogabe et al, 2015). There were 13 cross-sectional studies (Dunn, Xu & Schwimmer, 2008; Cotrim et al, 2009; Gunji et al, 2009; Hiramine et al, 2011; Dunn et al, 2012; Hamaguchi et al, 2012; Wong et al, 2012; Moriya et al, 2013; Sookoian, Castaño & Pirola, 2014; Kächele et al, 2015; Lau et al, 2015; Nishioji et al, 2015; Sogabe et al, 2015), two cross-sectional following longitudinal studies (Yamada et al, 2010; Moriya et al, 2015) and one cohort study (Hashimoto et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the end, 16 observational articles with a total of 76,608 participants including 39,198 nondrinkers, 31,942 light to moderate drinkers (LM drinkers), and 5,468 heavy drinkers met our inclusion criteria (Dunn, Xu & Schwimmer, 2008; Cotrim et al, 2009; Gunji et al, 2009; Yamada et al, 2010; Hiramine et al, 2011; Dunn et al, 2012; Hamaguchi et al, 2012; Wong et al, 2012; Moriya et al, 2013; Sookoian, Castaño & Pirola, 2014; Hashimoto et al, 2015; Kächele et al, 2015; Lau et al, 2015; Moriya et al, 2015; Nishioji et al, 2015; Sogabe et al, 2015). There were 13 cross-sectional studies (Dunn, Xu & Schwimmer, 2008; Cotrim et al, 2009; Gunji et al, 2009; Hiramine et al, 2011; Dunn et al, 2012; Hamaguchi et al, 2012; Wong et al, 2012; Moriya et al, 2013; Sookoian, Castaño & Pirola, 2014; Kächele et al, 2015; Lau et al, 2015; Nishioji et al, 2015; Sogabe et al, 2015), two cross-sectional following longitudinal studies (Yamada et al, 2010; Moriya et al, 2015) and one cohort study (Hashimoto et al, 2015). Of the studies, 10 were conducted in Asia (nine in Japan (Gunji et al, 2009; Yamada et al, 2010; Hiramine et al, 2011; Hamaguchi et al, 2012; Moriya et al, 2013; Hashimoto et al, 2015; Moriya et al, 2015; Nishioji et al, 2015; Sogabe et al, 2015) and one in Hong Kong (Wong et al, 2012)) and six in other countries (two in the US (Dunn, Xu & Schwimmer, 2008; Dunn et al, 2012), 1 in Brazil (Cotrim et al, 2009), 1 in Argentina (Sookoian, Castaño & Pirola, 2014) and 2 in Germany (Kächele et al, 2015; Lau et al, 2015)).…”
Section: Resultsmentioning
confidence: 99%